Patient voices in Britain, 1840-1948 - Hanley, Anne; Meyer, Jessica (Social Histories of Medicine, 2021)
In 1985 Roy Porter called for patients to be retrieved from the margins of history because, without them, our understanding of illness and healthcare would remain distorted. But despite concerted efforts, the innovation that Porter envisaged has not come to pass. Patient voices in Britain repositions the patient at the centre of healthcare histories. By prioritising the patient's perspective in the century before the foundation of the National Health Service, this edited collection enriches our understanding of healthcare in the context of Britain's emerging welfare state. Encompassing topics like ethical archival practice, life within institutions, user-driven medicine and the impact of shame and stigma on health outcomes, its chapters encourage historians to reimagine patienthood. It provides a model for using new sources and reading familiar sources in new ways. And, exploring traditional clinical spaces and beyond, it interrogates what it meant to be a patient and how this has changed over time. Crucially, the collection also aims to help historians locate and develop policy relevance within their work, reflecting on how these historical tensions continue to shape attitudes towards health, illness and the clinical encounter. Each chapter presents a framework for using history to speak to pressing policy issues.